2015
DOI: 10.7150/ijms.12133
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Myopic Shift among Primary School Children in Beijing, China: A Prospective Study

Abstract: Objective: To evaluate factors associated with myopic shift among primary school children.Methods: In a one-year prospective school-based study, 5052 children from ten schools were enrolled using a multi-stage random cluster approach. The baseline examination included non-cycloplegic auto-refractometry and questionnaire interview. Measurements were repeated at the follow-up.Results: Among 5052 students at baseline investigated, 4292 students (85.0%) returned for the follow-up examination. The mean refractive e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
51
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(57 citation statements)
references
References 32 publications
4
51
2
Order By: Relevance
“…In the analyses for possible risk factors for myopia, only parental myopia was associated with incident myopia and progression of SE, but not near work, outdoor activities or attending tutoring classes. The relationship between parental myopia and school myopia has been proposed in previous literatures . The present study found that as grade level increased, the strong association between parental myopia and progression of refraction (or incident myopia) decreased.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In the analyses for possible risk factors for myopia, only parental myopia was associated with incident myopia and progression of SE, but not near work, outdoor activities or attending tutoring classes. The relationship between parental myopia and school myopia has been proposed in previous literatures . The present study found that as grade level increased, the strong association between parental myopia and progression of refraction (or incident myopia) decreased.…”
Section: Discussioncontrasting
confidence: 99%
“…followed 643 primary schoolchildren for 4 years, and found that an increase in myopia is associated with parental myopia, less time outdoors and more time indoors . Another study in Beijing also reported 1‐year cohort in primary schoolchildren, and suggested that shorter distance from near work and shorter time outdoors were associated with an increase in incident myopia . Both of the two studies measured non‐cycloplegic refraction data, which will be inaccurate in evaluating young children's refractive status .…”
Section: Introductionmentioning
confidence: 82%
“…2013; Wu et al. ). Increased time outdoors was reported to be significantly associated with less myopic shift in these two studies.…”
Section: Resultsmentioning
confidence: 99%
“…; Wu et al. ) that investigated the association between outdoor time and a myopic shift in refractive error were excluded. Two of these studies investigated myopic shift in refraction in the overall sample (Guo et al.…”
Section: Resultsmentioning
confidence: 99%
“…9 Longitudinal studies in students of Beijing also found that close near work, less time on outdoor activities, and more time on indoor activities was significantly associated with more myopia progression. [10][11][12] Although daily activities are important environmental risk factors for myopic onset and its progression, [13][14][15][16] few studies have assessed the change of children's daily activities over time and their associated risk factors. French and co-authors reported that children in the Sydney Adolescent and Vascular Eye Study (SAVES) had significant decrease in amount of time on outdoor activities, and also had significant increase in near work time, in both 6-and 12-year-old cohorts, when re-examined 5 years later.…”
Section: Introductionmentioning
confidence: 99%